Performance budgeting. Reforming a complex adaptive system - Sinclair, Thomas A.P.; Mischen, Pamela (Journal of Public Governance, 2008)
The article discusses the determinants inherent in the implementation of performance budgeting in public sector administration. Relevant issues are analysed against the background of the principles of the new public management and the links between performance budgeting, strategic planning and management determination. The paper reviews various obstacles to performance budgeting. The Authors discuss the issues related to the system of performance measurement of public sector activity with a special focus on the ramifications of complex adaptive systems. A vital role in the process of performance budgeting is attributed to management at the operational level.